THE IMPLEMENTATION OF CORPORATE GOVERNANCE IN ISLAMIC BANKING IN INDONESIA BASED ON AAOIFI STANDARD - Ali Firmansyah Ashshiddiqy; Hartomi Maulana (Islamic Business and Management Journal, 2019)
This study aims to analyze the implementation of Corporate Governance in Islamic banking in Indonesia and the implementation of Corporate Governance in Islamic banking in Indonesia according to the standards of Corporate Governance by AAOIFI. This study used secondary data obtained from the annual report of Good Corporate Governance of Sharia Commercial Bank which has been published in 2016. The method used in this study is qualitative with the type of research is content analysis from the annual Good Corporate Governance report of Islamic bank in Indonesia. The results of this study indicate that the implementation of Corporate Governance at Sharia Commercial Banks in general have done good corporate governance which is marked with the result of self-assessment of every Sharia Commercial Bank which on average gets a good predicate. The results of research on the implementation of AAOIFI standards of Corporate Governance in general have applied some of the AAOIFI standards, but there is one standard AAOIFI that has not been applied by Sharia Commercial Banks other than Bank Muamalat. The standard that has not been applied is Internal Sharia Reviews which should be established in the policy. Thus it can assist the Sharia Supervisory Board and become the Liaison Officer between the Bank and the Sharia Supervisory Board in supervising the aspects of sharia regularly and helping to prepare the supervisory report of the Sharia Supervisory Board every semester which must be submitted to the Financial Services Authority (OJK). For further research, it is expected to re-analyze the implementation of Corporate Governance based on AAOIFI standard by using GCG report in several periods and to examine other components of the annual report and not only use AAOIFI governance standards.